2021
DOI: 10.1128/mbio.00463-21
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus Chimeras Expressing the Oropouche Virus Glycoproteins Elicit Protective Immune Responses in Mice

Abstract: Oropouche virus (OROV), an orthobunyavirus found in Central and South America, is an emerging public health challenge that causes debilitating febrile illness. OROV is transmitted by arthropods, and increasing mobilization has the potential to significantly increase the spread of OROV globally.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The PRVABC59 (Human/2015/Puerto Rico) strain of ZIKV was obtained from BEI Resources (NR-50240) from the Arbovirus Reference Collection (CDC, Fort Collins, CO, USA). VSV-OROV virus was generated as described previously ( 30 ). All of the viruses were propagated in Vero E6 cells with standard culture conditions using D2 media supplemented with 1% Pen/Strep and 1% l -Glut.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRVABC59 (Human/2015/Puerto Rico) strain of ZIKV was obtained from BEI Resources (NR-50240) from the Arbovirus Reference Collection (CDC, Fort Collins, CO, USA). VSV-OROV virus was generated as described previously ( 30 ). All of the viruses were propagated in Vero E6 cells with standard culture conditions using D2 media supplemented with 1% Pen/Strep and 1% l -Glut.…”
Section: Methodsmentioning
confidence: 99%
“…VSV-OROV was grown in BSR cells in DMEM media containing 2% FBS, as described previously ( 30 ). The supernatants containing the virus from two 150-mm dishes were collected, filtered, and concentrated by high-speed ultracentrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…The PRVABC59 (Human/2015/Puerto Rico) strain of ZIKV was obtained from BEI Resources (NR-50240) from the Arbovirus Reference Collection, CDC Fort Collins, CO, USA. VSV-OROV virus was generated as described previously (Stubbs et al, 2021). All viruses were propagated in Vero E6 cells (ATCC, CRL-1586) with standard culture conditions using D2 media supplemented with 1% Pen/Strep and 1% L-Glut.…”
Section: Methodsmentioning
confidence: 99%
“…The study also showed that the vaccine induced a robust immune response, with high levels of neutralizing antibodies detected in all vaccinated individuals. Furthermore, a recent study also explored the use of a replication-competent vesicular stomatitis virus (VSV) expressing OROV glycoproteins as a potential vaccine candidate ( Stubbs et al., 2021 ). This candidate vaccine was shown to protect mice from wild-type challenge, demonstrating its potential for human use.…”
Section: Vaccine Developmentmentioning
confidence: 99%